INTERACTIVE NAME DATABASES AS AN INTRODUCTION TO SOCIAL FACTORS AND GRAPH INTERPRET ATION. - BROOK, MARISA (American Speech, 2017)
The article talks about two data visualization tools that are linked to large databases of American first names and demonstrate how they can be used as an interactive introduction in an undergraduate class in sociolinguistics and/or dialectology. Topics discussed include the databases forming a versatile teaching aid that doesn't need to be confined to classrooms teaching variationist sociolinguistics specifically.